The Impact of Tourism Infrastructure and Marketing Strategies on Tourist Arrivals and Local Economic Growth in Bali - Jama, Ahmad Kamal; Yulianti, Yulianti; Prihatmadji, Wiwiet; Caniago, Aspizain; Izzah, Nidaul (Eastasouth Institute, 2024)
This study investigates the effect of tourism infrastructure and marketing strategy on tourist arrivals and local economic growth in Bali. Utilizing a quantitative research design, data were collected from a sample of 290 respondents using a Likert scale ranging from 1 to 5. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed to analyze the data and test the proposed hypotheses. The results indicate that both tourism infrastructure and marketing strategies have a positive and significant impact on tourist arrivals, which, in turn, contributes to local economic growth. The findings highlight the critical role of strategic investments in infrastructure development and marketing efforts in enhancing Bali's appeal as a global tourist destination. These insights provide valuable guidance for policymakers and stakeholders aiming to optimize the benefits of tourism and drive sustainable economic development in Bali.